1967
DOI: 10.1017/s0021859600017883
|View full text |Cite
|
Sign up to set email alerts
|

Fibre-type arrays and kemp succession in sheep

Abstract: A study of fibre-type arrays in relation to kemp succession in Kerry, Cheviot-cross and Swaledale lambs has been carried out. It is found that:1. There is a general association between HH grade and array such that higher grades tend to have stronger arrays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…The sudden decrease in size of fibres was found in the primitive and wild types of sheep (Dry, 1933(Dry, , 1934 and this pattern had been retained in the carpet types, whereas in the Merino the size order was upset (Burns, 1966). Guirgis (1964) found the precipice in most of the N-Type Romney plateau arrays. He concluded that where precipice occurred between HTCT and CT fibres, it supported Dry's (1933Dry's ( , 1934 conclusion that the precipice stands between the primary and secondary follicles.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The sudden decrease in size of fibres was found in the primitive and wild types of sheep (Dry, 1933(Dry, , 1934 and this pattern had been retained in the carpet types, whereas in the Merino the size order was upset (Burns, 1966). Guirgis (1964) found the precipice in most of the N-Type Romney plateau arrays. He concluded that where precipice occurred between HTCT and CT fibres, it supported Dry's (1933Dry's ( , 1934 conclusion that the precipice stands between the primary and secondary follicles.…”
Section: Discussionmentioning
confidence: 98%
“…The lower frequency of precipice within the CT group of the experimental flock might be due to the increase of saddle arrays, that occurred as a result of selection against kemp. Guirgis (1964), in a study of N-type Romney birthcoats, found that the precipice appeared to be reduced when the pre-natal check was more effective.…”
Section: The Second Group Of Barki Birthcoats {The Farmers' Flocks)mentioning
confidence: 98%
See 1 more Smart Citation
“…A small snippet was placed on black velvet and was visually divided into four types of fiber, i.e. fine (non-medullated), coarse (medullated), heterotype and kemp (more than 85% of cross sectional area as medulla) according to (Guirgis, 1967); unless than 300 fibers from each sample were used in this test. Benzene test was used to differentiate between coarse and fine fibers (Ryder and Stephenson, 1968).…”
Section: Wool Sampling and Measurementsmentioning
confidence: 99%
“…The higher frequency of saddle array might have accounted for the lower frequency of precipice encountered in the present Barki material. Guirgis (1964) reported a reduction in the frequency of precipice when the pre-natal check was more effective, in N-type birthcoats.…”
Section: Discussionmentioning
confidence: 99%